(untitled) (Mustansiria Dental Journal, 2018)
Bleaching the discolored teeth may affect the tooth/composite interface. This action found to be differing when different bonding agents were used. Aim of the study was to evaluate the effect of vital tooth bleaching on microleakage of existent class V composite resin restorations bonded with three dental bonding agents. Class V cavities were prepared on buccal surfaces of 60 intact, extracted human mandibular premolar teeth with gingival margins in cementum and occlusal margins in enamel, then these 60 teeth were randomly divided into 3 groups. Cavities in each group were treated with one of the following bonding agents: AdperTM Single Bond Pluse Adhesive (3M-ESPE) [group A], Tetric N-Bond (ivoclar, vivadent) [group T] and Stae (SDI) [group S]. All teeth were restored with Tetric N-Ceram light activated composite material. Each group was equally subdivided into control [AC, TC and SC] and bleached [AB, TB and SB] subgroups (n = 10). The bleached subgroups were bleached with 8% carbamide peroxide (Pola Paint, SDI, Australia) for 30 minutes twice a day for 14 days (according to the manufacturer’s instruction). Microleakage scores were evaluated on the incisal and cervical walls. Data were analyzed using Paired –Samples t- test. Bleaching with carbamide peroxide paint significantly increased the microleakage of composite restorations in Stae group at dentinal walls (P ≤0.05). Bleaching had no effect on microleakage of restorations in the AdperTM Single Bond Plus Adhesive and Tetric N-Bond groups. Vital tooth bleaching with carbamide peroxide paint has an adverse effect on marginal seal of dentinal walls of existent composite resin restorations bonded with Stae adhesive